DNA Copy Number Variations Characterize Benign and Malignant Thyroid Tumors - Liu, Yan (Endocrine Society, 2013)
CONTEXT: Fine-needle aspiration (FNA) is the best diagnostic tool for preoperative evaluation of thyroid nodules but is often inconclusive as a guide for surgical management. OBJECTIVE: Our hypothesis was that thyroid tumor subtypes may show characteristic DNA copy number variation (CNV) patterns, which may further improve the preoperative classification. DESIGN: Our study cohorts included benign follicular adenomas (FAs), classic papillary thyroid carcinomas (PTCs), and follicular variant PTCs (FVPTCs), the three subtypes most commonly associated with inconclusive preoperative cytopathology. SETTING: Tissue and FNA samples were obtained at an academic tertiary referral center. PATIENTS: Cases were identified that underwent partial or complete thyroidectomy for malignant or indeterminate thyroid lesions between 2000 and 2008 and had adequate snap-frozen tissue. INTERVENTIONS: Pairs of tumor tissue and matching normal thyroid tissue-derived DNA were compared using 550K single-nucleotide polymorphism arrays. MAIN OUTCOME MEASURE: Statistically significant differences in CNV patterns between tumor subtypes were identified. RESULTS: Segmental amplifications in chromosomes (Ch) 7 and 12 were more common in FAs than in PTCs or FVPTCs. Additionally, a subset of FAs and FVPTCs showed deletions in Ch22. We identified the 5 CNV-associated genes best at discriminating between FAs and PTCs/FVPTCs, which correctly classified 90% of cases. These 5 Ch12 genes were validated by quantitative genomic PCR and gene expression array analyses on the same patient cohort. The 5-gene signature was then successfully validated against an independent test cohort of benign and malignant tumor samples. Finally, we performed a feasibility study on matched FA-derived intraoperative FNA samples and were able to correctly identify FAs harboring the Ch12 amplification signature, whereas FAs without amplification showed a normal Ch12 signature. CONCLUSIONS: Thyroid tumor subtypes possess characteristic genomic profiles that may further our understanding of structural genetic changes in thyroid tumor subtypes and may lead to the development of new diagnostic biomarkers in FNA samples.